Draft Annual Plan (1982-83) Desert Development Agency District Kargil Govt. of Jammu and Kashmir - Planning Commission (Planning Commission, 1981)
Erstwhile combined District Ladakh represents a wide expanse of area consisting of Greater Himalayan Range. The entire area gives a rugged topography, bara rocks and intervening deposits and avoid of vegetational cover arctic cold and dry climate that is totally in hospitable an environment for human habitation resulting in its socio-economic plight. The State Government for administrative reasons split-up this District and in July, 1979 was carved out and came into being the present District of Kargil (Area 15086 Sq-Kms).
Govt. of Jammu and Kashmir, Planning and Development Deptt.